Computer-aided design of graphene and 2D materials synthesis via magnetic inductive heating of 11 transition metals. (30th November 2021) - Dhaouadi, Elyes; Hinkov, Ivaylo; Pashova, Katya; Challab, Nabil; Roussigné, Yves; Abderrabba, Manef; Farhat, Samir
Abstract: We performed numerical simulations to determine the effect of the most influential operating parameters on the performance of a radio frequency (RF) induction-heating system in which RF magnetic fields inductively heat metal foils to grow graphene. The thermal efficiency of the system depends on the geometry as well as on the materials' electrical conductivity and skin depth. The process is simulated under specific graphene and two-dimensional (2D) materials growth conditions using finite elements software in order to predict the transient temperature and magnetic field distribution during standard graphene and 2D materials growth conditions. The proposed model considers different coil Helmholtz-like geometries and 11 metal foils, including Ag, Au, Cu, Ni, Co, Pd, Pt, Rh, Ir, Mo, and W. In each case, an optimal window of process variables ensuring a temperature range of 1035 °C–1084 °C or 700 °C–750 °C suitable for graphene and MoS2 growth, respectively, was found. Temperature gradients calculated from the simulated profiles between the edge and the center of the substrate showed a thermal uniformity of less than ∼2% for coinage metals like Au, Ag, and Cu and up to 7% for Pd. Model validation was performed for graphene growth on copper. Due to its limited heat conductivity, good heating uniformity was obtained. As a consequence, full coverage of monolayer graphene on copper with few defects and a grain domain size of ∼2 µ m was obtained. The substrate temperature reached ∼1035 °C from ambient after only ∼90 s, in excellent agreement with model predictions. This allows for improved process efficiency in terms of fast, localized, homogeneous, and precise heating with energy saving. Due to these advantages, inductive heating has great potential for large-scale and rapid manufacturing of graphene and 2D materials.